Genome-wide Association Study Identifies Five Susceptibility Loci for Follicular Lymphoma outside the HLA Region - Skibola, Christine F.; Berndt, Sonja I.; Vijai, Joseph; Conde, Lucia; Wang, Zhaoming; Yeager, Meredith; de Bakker, Paul I.W.; Birmann, Brenda M.; Vajdic, Claire M.; Foo, Jia-Nee; Bracci, Paige M.; Vermeulen, Roel C.H.; et al. (American journal of human genetics, 2014)
Genome-wide association studies (GWASs) of follicular lymphoma (FL) have previously identified human leukocyte antigen (HLA) gene variants. To identify additional FL susceptibility loci, we conducted a large-scale two-stage GWAS in 4,523 case subjects and 13,344 control subjects of European ancestry. Five non-HLA loci were associated with FL risk: 11q23.3 (rs4938573, p = 5.79 × 10−20) near CXCR5; 11q24.3 (rs4937362, p = 6.76 × 10−11) near ETS1; 3q28 (rs6444305, p = 1.10 × 10−10) in LPP; 18q21.33 (rs17749561, p = 8.28 × 10−10) near BCL2; and 8q24.21 (rs13254990, p = 1.06 × 10−8) near PVT1. In an analysis of the HLA region, we identified four linked HLA-DRβ1 multiallelic amino acids at positions 11, 13, 28, and 30 that were associated with FL risk (pomnibus = 4.20 × 10−67 to 2.67 × 10−70). Additional independent signals included rs17203612 in HLA class II (odds ratio [ORper-allele] = 1.44; p = 4.59 × 10−16) and rs3130437 in HLA class I (ORper-allele = 1.23; p = 8.23 × 10−9). Our findings further expand the number of loci associated with FL and provide evidence that multiple common variants outside the HLA region make a significant contribution to FL risk.